On the issue of system methodology crisis and ways to overcome it - Доценко, Сергей Ильич (Technology audit and production reserves, 2014)
An analysis of general systems theory problems is conducted in the paper. It is shown that the introduction of an additional category of “management” does not solve the problems of an unambiguous definition of the category of “system”. The necessity to introduce the category of “activity” is demonstrated. The possibility to determine the meaning of the category of “activity”, different from the meaning of the category of “process” is substantiated. For the category of “process”, the feature of its meaning is the result of the process realization. It always has a certain meaning. Provisions of the theory of functional systems, developed by academician P. Anokhin have served as the basis for determining the category of “activity”. Based on this theory, four organizational tasks, solution of which constitutes the “unit” of the integrated activity of the organization are introduced. The distinctive feature of implementing the “unit” of the integrated activity is the constancy of the activity result. This result is expressed in the equality to zero between the features of the project of future result and its actual results. Subject of wildlife is organization if and only if it is able to implement the “unit” of the integrated activity in the form of four organizational tasks. These tasks are realized in its two parts. These parts may be represented as systems. In this case, wholeness is not required of the system, it is enough to obtain a concrete final result of implementing the processes, included in it. System can be defined as a set of interacting elements, ensuring solving organizational tasks. Thus, it is possible to determine unambiguous meaning for the categories of the “whole” and “system” and their relationship - the “whole” and the “part”.